Epidemiology of paraneoplastic neurologic syndromes and autoimmune encephalitides in France. Issue 6 (November 2020) - Hébert, Julien; Riche, Benjamin; Vogrig, Alberto; Muñiz-Castrillo, Sergio; Joubert, Bastien; Picard, Géraldine; Rogemond, Véronique; Psimaras, Dimitri; Alentorn, Agusti; Berzero, Giulia; Desestret, Virginie; Rabilloud, Muriel; et al.
Abstract : Objective: To determine the observed and expected incidence rates of paraneoplastic neurologic syndromes (PNSs) and autoimmune encephalitides (AEs) diagnosed in France between 2016 and 2018, we conducted a population-based epidemiologic study. Methods: Observed incidence rates were stratified by sex, age groups, region of care, year of diagnosis, and disease subgroups. National expected incidence rates were calculated based on rates obtained in the area directly adjacent to the Reference Center using a mixed Poisson model and compared with observed incidence rates. Results: Six hundred thirty-two patients with definite PNS or AE met the inclusion criteria. The observed incidence rate of definite PNS and AE in France was 3.2 per million person-years (CI95% : 2.9–3.4) compared with an expected incidence rate of 7.1 per million person-years (CI95% : 3.9–11.4). The national observed incidence rate for the antibody-positive AE subgroup increased from 1.4 per million person-years (CI95% : 1.2–1.7) in 2016 to 2.1 per million person-years (CI95% : 1.7–2.4) in 2018, thus surpassing the incidence rate of classical PNS (1.2 per million person-years [CI95% : 1.0–1.5]) of 2018. Conclusions: There was a significant widespread year-to-year increase in the incidence of diagnoses registered with the Reference Center for all subgroups of PNS and AE studied. The national observed incidence rate is likely underestimated due to underdiagnosis and underreporting.